Effect of egg freshness on texture and baking characteristics of batter systems formulated using egg, flour and sugar. (17th August 2015) - Xing, Liting; Niu, Fuge; Su, Yujie; Yang, Yanjun
Abstract: BACKGROUND: The aim of this work was to evaluate the effects of egg freshness on baking properties and final qualities in batter systems. Batters were made with eggs of different freshness, and the properties of batter systems were studied through rheological analysis, rapid viscosity analysis (RVA), differential scanning calorimetry (DSC), batter density and expansion rate during the baking and cooling processes. Moreover, the qualities of final baked systems were investigated, including specific volume and texture profile analysis (TPA). RESULTS: The flow behavior of batters showed that the consistency index ( K ) decreased as the Haugh unit (HU) value decreased, while the flow behavior index ( n ) increased. Both the storage modulus ( G ′) and loss modulus ( G ″) determined by mechanical spectra at 20 °C decreased with decreasing HU. RVA and DSC determinations revealed that lower‐HU samples had a lower viscosity in the baking process and a shorter time for starch gelatinization and egg protein denaturation. Observation of the batter density revealed an increasing change, which was reflected by a decrease in the specific volume of final models. TPA showed significant differences in hardness and chewiness, but no significant differences in springiness and cohesiveness were found. CONCLUSION: The egg freshness affected the properties of batter systems. © 2015 Society of Chemical Industry